Proceedings of the International Conference on Public Administration, Policy and Governance (ICPAPG 2019) 2020
DOI: 10.2991/aebmr.k.200305.221
|View full text |Cite
|
Sign up to set email alerts
|

The Student’s Ability to Read the Qur’an at Islamic Education Program Universitas Negeri Padang (A Need Assessment Study)

Abstract: The research aims to describe the student's ability to reading Al-Qur'an at the department of Islamic Education at Social Sciences Faculty, Universitas Negeri Padang. This research uses a quantitative method, where data were collected by test to 130 students of 2017. Then, data were analyzed by statistical analysis using SPSS 22. Respondents read the specified verses of the Al-Qur'an. The reading of these verses is checked based on the rules in reading Al Qur'an, especially makharijul hurf, the law of nun and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…26 A study in Islamic studies indicated that half of the students' abilities are still not good in reading the Qur'an following tajwid rules. 27 It recommends designing effectively and efficiently the Qur'an learning. The duration of reading the Qur'an should be improved while it has relation for coping the stress and better learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…26 A study in Islamic studies indicated that half of the students' abilities are still not good in reading the Qur'an following tajwid rules. 27 It recommends designing effectively and efficiently the Qur'an learning. The duration of reading the Qur'an should be improved while it has relation for coping the stress and better learning outcomes.…”
Section: Discussionmentioning
confidence: 99%